“I’ve never belonged to anybody—not really”: Space, place, and the bildungsroman in L. M. Montgomery’s Anne of Green Gables (1908) - Ashley N. Reese; Erin Spring (Barnelitterært Forskningstidsskrift, 2022)
Drawing on the work of geographers Yi-Fu Tuan and Edward Relph, this article takes up concepts such as place, space, rootedness, insideness, and outsideness to argue that, in L. M. Montgomery’s Anne of Green Gables (1908), Green Gables (both the farm and the house) are central to protagonist Anne’s identity. As Anne grows up, she moves from an orphan heroine (space, outsideness) to someone with a family and a permanent home (place, insideness, rootedness), completing the girl’s bildungsroman arc of joining her community through belonging. Using children’s literature’s home-away-home narrative as a framing device, we argue that, in this text, Anne chooses her love of place (topophilia) for Green Gables and consequently, domesticity over furthering her education, fulfilling the girl’s bildungsroman trajectory.